Plotinus : A Bibliography 1950-2000 - Dufour, Richard (Brill Book Archive Part 1, ISBN: 9789004472495., 2002)
The aim of this book is to help teachers and students in Ancient philosophy to find their way into the vast amount of modern publications about Plotinus. It collects over 50 years of research in a single and easy-to-use book, containing over 1500 entries in all languages. The first part deals with modern translations of Plotinus' treatises, while the second part lists studies concerning particular aspects of Plotinus' thought. The work ends with a series of 4 indexes allowing the reader to find any references quickly. This bibliography contains all the entries that have been listed in the different existing bibliographical indexes. These entries have been corrected and completed with small summaries when necessary. This bibliography is the most exhaustive one now available for those interested in plotinian studies.